VONIS DAN KEKALAHAN AHOK BEREFEK LUAS TERHADAP ELEKTABILITAS PARTAI PDI PERJUANGAN - Ekawati, Ekawati (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2017)
The aim of this research is to know the effect of the loss of Ahok and Jarot in the general election in DKI Jakarta. The method of the research is qualitative by taking the references from some books, newspaper and magazine namely Tribun Kaltim Kaltim Post,Gatra and the others .The results of the research are (1).The supporters including the support of the Political Party involves the religion domain,(2). The supports of the Political Party do not avoid the actors of the   religion followers who are the actors involved in the general election ;(3).The Voters should be given  the religion aspects.(4).The loss of the couple Ahok and Jarot caused by religion domain; (5).The couple who get the victory because  the religion centiment;(6).The winner will be gentlement because they       will end happily and fairly and the couple of Ahok-Jarot has to be ensured that  the  income does never  exchanged.The suggestions in  this  results are (1).The Political party supporters have to support based on political affairs ,(2). The Political party supporters not enter the religion affairs (3).The commisioners of KPU have to sentence to whoever relates the politics and religion in the compaign ,(4).The loss does not any relate with others but political affairs,(5).The supporters do not get any profit but to play fairly,(6).The all sides in the society has to keep it peaceful.,(7).General election is just competition not a war.